Palm oil mill effluent treatment using aerobic submerged membrane bioreactor coupled with biofouling reducers - Yuniarto, Adhi (2015)
The existing palm oil mill effluent (POME) treatment is often still difficult to adhere to the effluent standards. One of the most promising novel technologies in wastewater treatment system is the membrane bioreactor (MBR). The aim of this study is to treat POME using aerobic submerged membrane bioreactor (ASMBR) system to improve the effluent quality before biofouling reducer (BFR) is applied to reduce the membrane fouling. Diluted POME was treated with a 20 L lab-scale ASMBR equipped with a single microfiltration flat sheet membrane module. The ASMBR systems with mixed liquor suspended solids (MLSS) from 3000 to 12,000 mg L-1 and solids retention time (SRT) from 20 days and above were used to investigate the best operating condition of the system without BFR. The finding shows ASMBR continuous system operated at MLSS of 9000 mg L-1 and SRT of 20 days to produce good quality effluent, less microbial products, and moderate membrane fouling rate. Since membrane fouling is the main obstacle in the membrane system, powdered activated carbon (PAC), granulated activated carbon (GAC) and zeolite (ZEO) were added to the ASMBR as BFR. Batch tests with BFR concentrations from 1 to 10 g L-1 were used to determine the best BFR dose. It can be concluded that 4 g L-1 of PAC, GAC, and ZEO is the best BFR dose to produce good residual organic contents and colour of final products. Furthermore, the performance of ASMBR without BFR (called BFR0) and coupled with BFR were compared by assessing the removal efficiencies of organic and colour, the fouling phenomenon propensity, and the critical flux (Jc) enhancement. The systems were subjected to two batches of organic loading rate (OLR), equal to about 1000 and 3000 mg COD L-1. Each system with BFR showed distinct performances by producing higher effluent quality as compared with BFR0. On both OLR, the ASMBR systems with BFR removed organic constituents with more than 96%, produced effluent with average residual colour of less than 55 ADMI and significantly increased Jc up to 42 L m-2 h-1. It can be concluded that PAC is the best BFR for ASMBR system to treat POME by producing the highest quality of effluent, distinct changes in the concentrations of soluble microbial products (SMP) and extracellular polymeric substances (EPS), formed lowest operational trans-membrane pressure (TMP), and produced highest Jc. Finally, the experimental results were verified using activated sludge models no. 1 (ASM1) by also conducting the COD fractionation and respirometric analysis. The stoichiometry and kinetic parameters were determined to describe the bioprocess of the system. The COD fractionation of POME indicated dominant fraction of slowly biodegradable matters (42-56%). Oxygen utilization rate (OUR) of the ASMBR systems was found to fit well with ASM1 results. Compared with BFR0, the addition of BFR increased the stoichiometry parameter of YH up to 0.49 mg cell COD mg-1 COD, increased the kinetic parameters of µmaxH, and µmaxA up to 1.6 and 0.48 d-1, respectively, and increased KO,H and KO,A up to 0.59 and 0.82 mg COD L-1, respectively. The value of bH and KS were decreased to 0.32 d-1 and 0.89 mg COD L-1, respectively. These sets of model parameters were verified describing the enhancement of bioprocess in the ASMBR system coupled with BFR.